VCO sebagai Alternatif Produk Ekonomi Berbasis Alam: Kontribusi bagi Masyarakat dan Lingkungan - Andin, Andhini Wulandari; Muhammad Rafli; Muh. Nur Ikhsan Jufri (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
The use of coconut in the form of VCO not only provides economic benefits to the community, but also contributes to environmental conservation efforts. Natural products are considered safer, healthier, and more environmentally friendly than synthetic products. One of the natural resources that can be utilized is Virgin Coconut Oil (VCO). The researcher first explains the relationship between one variable and another in this context variable one is the producer (VCO maker) and the other variable is the consumer (community). Then the status of a group or variable will be described and by exploring the information that is needed in the research process. This study was conducted to explore more deeply the potential of Virgin Coconut Oil (VCO) as a natural health product in the Bontoharu Village area, Rilau Ale District, Bulukumba Regency, and to analyze its contribution to the environment. Bontoharu Village has abundant coconut resources, which are the basic ingredients for making VCO. Through education and training, the community can better understand the benefits of VCO and its environmentally friendly production techniques.